The Comparison of Water Spinach (Ipomoea aquatica) Density Using Aquaponic System Through Reduced Concentration of Ammonia (NH3), Nitrite (NO2), Nitrate (NO3) And Its Influence On Conversion Rate and Feed Efficiency To Increase The Survival Rate And Growth Rate of African Catfish (Clarias sp.) Intensive - Prayogo Prayogo (Department of Aquaculture, 2019)
In intensive aquaculture farming activities will generate solid waste and liquid waste that comes from feces and leftover fish feed. The waste accumulation can lead to deterioration of water quality that affects the physiological processes, behavior, growth, and mortality of fish. Technological innovation is needed for the management of water quality and increase productivity as a result of shrinkage of cultivated land. One of the technological innovations that can be applied, namely the incorporation of fish farming with crops through Aquaponics system. This study aims to determine the effects of water spinach optimum density to absorb waste ammonia (NH3), nitrate (NO3) and nitrite (NO2) optimally to increase the survival rate and growth rate of african catfish (Clarias sp.) intensive As well as to see its effect on conversion rates and feed efficiency with aquaponics system. The method used is the experimental method. The experimental research is used to determine the effect of certain variable towards a group under controlled conditions. The results of measurements of ammonia levels during P0 showed that the treatment significantly different (p <0.05) with treatment P1; P2; and P3. P3 treatment with water spinach number 40 stems provide maximum results in lowering the concentration of ammonia compared with treatment P0 (without spinach), P1 (20 water spinach), and P2 (30 water spinach). The measurement results nitrite levels during the observation showed that all treatments there were no significant differences (p> 0.05). The measurement results also showed that the nitrate content whole of observation results showed that all treatments there were no significant differences (p> 0.05). The best feed conversion ratio was found in P3 treatment of 1.08. The best feed efficiency was found in P3 treatment 92,25%. The highest survival rate was found in P3 treatment (88.69%) in maintenance medium and lowest survival rate was in P0 treatment (26,71%) without water spinach (control). The highest specific growth rate was found in P3 treatment (1.15%), while the lowest specific growth rate was in treatment P0 (0.79%).Results of water quality measurement supporting all treatments decreased and increased. The supporting water quality are temperature, pH, and dissolved oxygen. The decrease and increase in support water quality is caused by environmental factors such as weather. Other parameters were observed in addition to supporting the water quality is water spinach plant growth. Value growth water spinach is best found in treatment P3. In the treatment P3 water spinach growth rose 5.14 cm with an initial size of 10.92 into 16.06.